2021
DOI: 10.1016/j.xplc.2020.100113
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome-level reference genome assembly for Panax notoginseng and insights into ginsenoside biosynthesis

Abstract: Panax notoginseng , a perennial herb of the genus Panax in the family Araliaceae, has played an important role in clinical treatment in China for thousands of years because of its extensive pharmacological effects. Here, we report a high-quality reference genome of P. notoginseng , with a genome size up to 2.66 Gb and a contig N50 of 1.12 Mb, produced with third-generation PacBio sequencing technology. This is the first chromosome-level genome assembly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 74 publications
(33 reference statements)
1
58
0
Order By: Relevance
“…Four versions of P. notoginseng genome assembly have been reported (Chen et al, 2017; Fan et al, 2020; Jiang et al, 2020; Zhang et al, 2017). The first two assemblies are highly fragmented, which limits genomic studies of P. notoginseng .…”
Section: Figurementioning
confidence: 99%
“…Four versions of P. notoginseng genome assembly have been reported (Chen et al, 2017; Fan et al, 2020; Jiang et al, 2020; Zhang et al, 2017). The first two assemblies are highly fragmented, which limits genomic studies of P. notoginseng .…”
Section: Figurementioning
confidence: 99%
“…Jiang et al reported a significantly improved chromosome-level assembly of P. notoginseng . The 2.66 Gb reference genome has a scaffold N50 of 216.47 Mb with 37,606 genes annotated (Jiang et al 2020 ). The assembly statistics of the P. ginseng and P. notoginseng genome are provided in Table 1 .…”
Section: Status Of Genomic Research In the Genus Panaxmentioning
confidence: 99%
“…In 2017, Zhang et al completed a 1.85 Gb whole genome with a scaffold N50 of 157.81 kb and annotated 34,369 genes (Zhang et al 2017). In the same year, Chen et al reported a 2.39 Gb whole genome sequence with a scaffold N50 of 96 kb, annotating 36,790 genes (Chen et al 2017 (Jiang et al 2020). The assembly statistics of the P. ginseng and P. notoginseng genome are provided in Table 1.…”
Section: Status Of Genomic Research In the Genus Panaxmentioning
confidence: 99%
“…3 ). Four to twelve SE isoforms were predicted in P. ginseng 98 , 99 and five isoforms were in P. notoginseng 100 . PnSE1 and PnSE2, belonging to two separate large groups, were similar to PgSE1 and PgSE2, respectively 95 .…”
Section: Biosynthetic Pathways Of Ginsenosidesmentioning
confidence: 99%